University Strategic Planning in Cameroon - Ngwana, Terfot Augustine (Education Policy Analysis Archives, 2003)
This article argues that the global, regional, and local realities can complement rather than contradict each other in the process of strategic planning for universities in Sub-Saharan Africa (SSA). Using the case of the University of Buea in Cameroon, it attempts to use the global trends of polarisation in knowledge production capacity as an input or tool for identifying strategic choice in the process of strategic planning in institutions. The national policy background is used to highlight the context and inherent role of the central government in the process of institutional strategic planning.